Evidenzbasierte Stimmtherapieprogramme bei Dysphonien: eine Literaturstudie - Barsties v Latoszek, Ben (Sprache · Stimme · Gehör, 2020)
The aim of the present study was a systematic literature review on selected evidence-based voice therapy programs for the treatment of various types of dysphonia. The results showed that nine of seventeen voice therapy programs complied the selection criteria. All nine voice therapy programs revealed significant improvements in various aspects of laryngeal evaluation, voice quality, vocal function, and/or self-evaluation. These improvements might be expected between one day to ten weeks. Mostly, the voice therapy programs based on physiological voice therapy.
Keywords: Stimmtherapie; Dysphonie; Therapieeffekte; systematische Literaturstudie; Therapieresultate